Depiction of a four-armed Bhairav - Temples of India Project Team (Jio Institute, 2024)
The only major image depicting the divinity of Shiva is a four-armed portrayal of Bhairav on a temple shaft near the entrance of the temple, in the mandapa, and is practically the first religious image one encounters when visiting the temple. He wears the necklace of a serpent, but other identifying attributes have deteriorated over time. His heavily jeweled naked body clearly reveals his genitalia.